Human herpes virus-8-associated multicentric Castleman's disease in an HIV-positive patient presenting with relapsing and remitting hyponatraemia. (October 2015) - Sasaki, Hiroaki; Maeda, Takuya; Hara, Yu; Osa, Morichika; Imai, Kazuo; Moriguchi, Kota; Mikita, Kei; Fujikura, Yuji; Kaida, Kenichi; Kawana, Akihiko
We report a case of human herpes virus-8-associated multicentric Castleman's disease in an HIV-positive patient with hyponatraemia. A 65-year-old man was admitted with relapsing and remitting fever, scattered skin eruptions and hepatosplenomegaly following combination antiretroviral therapy for his HIV infection. Based on histopathological findings, he was diagnosed as having human herpes virus-8-associated multicentric Castleman's disease and was treated with four-weekly infusions of rituximab. Prior to receiving chemotherapy, we observed several suspected biomarkers of disease activity, positive correlations between plasma human herpes virus-8 viral load and the levels of plasma interleukin-6, C-reactive protein and soluble interleukin-2 receptor, and negative correlations between platelet count, albumin levels and especially serum sodium levels. We hypothesize that non-osmotic release of plasma antidiuretic hormone is a cause of hyponatraemia in human herpes virus-8-associated multicentric Castleman's disease and that relapsing and remitting hyponatraemia could be correlated with plasma human herpes virus-8 viral load.